TEACHING SENIOR HIGH SCHOOL STUDENTS TO WRITE PROCEDURE TEXTS BY USING SMALL GROUP DISCUSSION - Beto Andrias; Saunir Saun (Universitas Negeri Padang, 2017)
The teacher can use small group discussion in teaching writing procedure text in the teaching and learning process. By applying this method, the students can get interest and understanding procedure text well. The objective of this paper is to help the students to organize their ideas and write their ideas in a good order. Besides, the teacher also has to give more time for teaching writing especially in teaching text in order to increase the students’ ability in writing procedure text. Writing procedure texts through small group discussion bring the students to new kind of situation. It would help both the teacher and students to revise the students’ writing and made writing more fun than the way it used to be.